A transcription factor modulates dermal architecture to generate structural and pigment color diversity in lizards - Prem Aguilar; Pedro Andrade; Jindřich Brejcha; Paulo Pereira; Roberto Arbore; Javier Abalos; Sandra Afonso; Rita Afonso; Arnaud Badiane; Enrique Font; Giulia Simbula; Zuzana Bosakova; et al. (Proceedings of the National Academy of Sciences, 2026)
The way organisms perceive the world influences their evolution. Many animals detect ultraviolet (UV) light invisible to humans, creating sensory contexts that alter the selective landscape for coloration. Here, we dissected the molecular basis of a UV-reflecting color morph in common wall lizards, uncovering its association with a noncoding region upstream of the transcription factor PAX7 . Our results suggest that variation at this locus alters dermal architecture by modifying the cellular composition, exposing structures within specialized cells that generate UV structural coloration. We further demonstrate that the PAX7 locus acts epistatically on other color genes to suppress pigment deposition, revealing a genetic interaction between pigmentary and structural pathways that underlie color production. Across populations, the frequency of the UV morph was not predicted by environmental variation, arguing against climate-driven selection. Inferred frequencies of the UV-associated allele across sampled populations exhibited weaker spatial structure than expected from genome-wide variation, suggesting this polymorphism may be maintained by balancing selection. Our findings reveal mechanisms of phenotypic evolution beyond human perception and a genetic link between pigmentary and structural coloration.